Simulasi Perbandingan Performansi Protokol Routing Proactive, Reactive Dan Hybrid Pada Vehicular Ad Hoc Network (VANET) Di Kota Pekanbaru - Fitriani Saputri; Linna Oktaviana Sari; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Vehicular Ad-Hoc Network (VANET) is a development of the Mobile Ad-Hoc Network (MANET) which makes the vehicle its node. VANET technology is expected to improve driver safety when driving. VANET has network characteristics that change rapidly due to fast node movement. Therefore, VANET requires a routing protocol that is considered suitable and efficient so that sending data packets can take place optimally. This research simulated and analyzed the performance comparison of proactive routing protocol (DSDV), reactive routing protocol (AOMDV) and hybrid routing protocol (ZRP) on VANET in Pekanbaru city. This simulation was carried out using NS-2.35 and SUMO as a mobility generator. Performance is measured using comparison parameters in the form of Packet Delivery Ratio, End to End Delay, and Routing Overhead. The results show that the AOMDV routing protocol is better than Packet Delivery Ratio parameter values with an average value of 99.9%. DSDV routing protocol is better than End to End Delay parameter values with an average value of 0.09 s. While the ZRP Routing Protocol is better than Overhead Routing values with an average value of 0.500. Thus, the protocols have their respective advantages. Keyword: VANET, Proactive, Reactive, Hybrid, NS-2.35, SUMO, DSDV, AOMDV, ZRP, Pekanbaru